SUICIDE AS A RESULT OF RELIGIOUS TRAUMA IN COPPOLA’S THE VIRGIN SUICIDES - Yunita, Tiara Rachma; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
The objective of this research is to examine the disproportionate id and superego that results in religious trauma, which is the trigger of the Lisbon sisters to commit suicide. To conduct this research, qualitative method was used to analyze The Virgin Suicides (2000) by Sofia Coppola. Following the investigation, the researcher identified five elements that contributed to the sisters' religious trauma throughout the film.